Galactagogue Herbs - ยิ้มแย้ม, สุสัณหา (Nursing Journal CMU, 2018)
Although breast milk is the best food for newborn, many postpartum mothers often having difficulty with breastfeeding initiation to their infants. The important problem that the mother identified as the cause of early introducing formula and/or premature weaning from breast is perceived insufficient breast milk. Some mothers have trying to solve this problem by using galactagogues for stimulating breast milk production. Herbs as a natural products have been used to promote health and it is widely used among lactating women. This is a traditional practice have been told from generation to generation and believed that it is safe, and no risk of maternal and child health. Although the current interest in the use of the herb during lactation is worldwide increasing issue. However, it is lack of the information about galactagogue herbs in terms of its action, biochemical and physiological effects, stimulating breast milk production as well as the appropriate quantity of the herbs for increasing breast milk volume and consequent effects on infant. In addition, the use of the herbs that still be incorrect information, it should be avoid. Therefore, the study on galactagogue herbs is necessary. It should be included a vriety types of herbs that use as food or other products such as tea herbs, the ready to drink beverages, herb beverage instant, etc.